National Health Insurance in Indonesia and Its Impact on Health-Seeking Behavior - Setyawati, Any (Animo Repository, 2021)
The purpose of this study was to assess the impact of Indonesia’s National Health Insurance (NHI) on health care utilization. Specifically, by performing logistic regressions with the national socioeconomic data of 2018, we analyzed health-seeking behavior between insured and inunsured people together with selected socioeconomic factors. The results revealed that insured people were more likely to utilize the NHI services than uninsured people. Additionally, the utilization pattern was more significant in socially vulnerable groups, particularly lower-income, lower-educated, unemployed, and rural beneficiaries. Assuming that one of the ultimate goals of social health insurance is to enhance the equity of health care utilization by lowering the financial burden of health care for the marginalized population, the results indicate that the NHI adequately accomplished the equity goal. However, we also noticed a considerable policy gap between the need for and availability of the NHI services. That is, although the NHI offered almost free services, a large proportion of beneficiaries still relied heavily on self-medication and private facility care, which required out-of-pocket costs. To reduce the gap, the government should continue its efforts to improve the current inadequacy of health care financing and infrastructure in the public sector, accompanied by more empirical investigations.